Distribution of Vam Fungi in Bauxite Mine overburden Plantation of Amarkantak (Madhya Pradesh) - , Jamaluddin; Chandra, K. K (Indian Forester, 1997)
The study of VAM fungi was made in the plantations under taken in bauxite mine area. Initially Bauxite mine overburden soil is deficient in VAM fungi but the plantations enhance the VAM population. The VAM colonization and spore density vary in different species even in different age group of same species. The population of VAM fungi was more in undisturbed plantation in forest area, as compared with the species planted after mining. The growth and development of species was more in the plantation undertaken in the degraded forest area without mining operations.